Study of the Thermal Neutrons& Γ-Irradiatation on the Optical Constants of Pm-355 - Al-Mashhadani, Nahida J H (Al-Nahrain Journal of Science, 2012)
The optical reflection, transmission,and UV/VIS- absorption spectra had been recorded in the wavelength(200-500nm) for PM-355 before and after irradiation with thermal neutrons by using (Am-Be)neutron sourceof flux (5000n/cm2 .Sec) for a week,then γ-ray irradiation by using 60Co-dose within range of(20-120Mrad) at normal conditions. The absorption spectra of irradiated samples showed radiation induced absorption changes by photodegradation.There was an increment in absorption proportional with irradiation dose.It is attributed to the interfaces traps, which are formed by thermal neutrons & γ-irradiation. It was found that the absorption and reflectance spectra were in opposite behavior of transmittance.The optical constants (α,Kex,n,ε,Eg,ΔE, and Eu) were calculated for all samples.The effect of irradiation on the optical constants of the PM-355 before and after irradiation had been discussed and investigated